A formação profissional do assistente social na residência multiprofissional em saúde do HU/UFS - Andrade, Kércia Rocha (2015)
The Multidisciplinary Residency in Health (Remu) was established by Decree No. 2117 of November 3, 2005, complementing Law No. 11,129 of June 30 of that year. It established the Scholarship Program for Education through Labor and the National Commission on Multidisciplinary Residency in Health (CNRMS). Created as post-graduation sensu, the Remu is in a new type of professional in-service training, targeted to health professionals. This study aims to analyze the contributions of the Residency Program in Multidisciplinary Integrated Adult and Elder health, of the University Hospital, Federal University of Sergipe (Remu/HU/UFS), for the training of social workers. This is a recent theme and in a still growing process of research for health professionals, especially for social work. Here we highlight the multidisciplinary educational process, their functions, powers, and the contribution of this kind of training for the social worker. Therefore, it was necessary to assess the implications of service training for this professional inserted in Remu/HU/UFS; analyze how this type of teaching that involves different areas of knowledge influences the formation of the social worker; and check the main advances and challenges of Remu/HU/UFS for residents of Social Services. It is a qualitative research and exploratory nature, which has the historical and dialectical materialism as a guiding method. It has been used the bibliographical (journals, books, monographs, dissertations, theses, articles, etc.), documentary (by analysis of the political-pedagogical project Remu/HU/UFS) and the field research (through interviews). The interview, the semi-structured type, was carried out with the graduates of 2012-2014 class residents and those who are attending the class residence in 2013-2015, totaling 07 (seven) interviewed. Despite the challenges imposed by the neoliberal policies through the counter-reformation process of the Brazilian State and the dismantle of the social policies (especially health and education), difficulties in the consolidation and recognition of residence within the UFS, the study identified that the Remu/HU/UFS has contributed to the training of social workers. The research points the need to promote new attempts of dialogue with the Departments of the Federal University of Sergipe, the constant reflection of the training model service established by the program and its contributions to the training of social work professionals.